PENGARUH GAYA BELAJAR TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI BONTORAMBA MAKASSAR - Astuti, Nur Fauji; Maryam; Firdaus, Andi Mulawakkan (Almeera Education, 2023)
This study aims to determine the effect of student learning styles on learning achievement. this research uses a type of quantitative research with ex post facto. Data collection using questionnaires and documentation. Data analysis techniques using inferential statistics. The population was all students of SD Negeri Bontoramba Makassar and the sample used purposive sampling, namely grade VI students. The results of the study, namely: (1) There is no positive influence of visual learning style on learning achievement with a significance value of 0.619 and 0.811. (2) There is a positive effect of auditory learning style on learning achievement with a significance value of 0.019 and 0.012. (3) There is no positive effect of kinesthetic learning style on learning achievement with a significance value of 0.619 and 0.81. (4) There is no influence and significant visual, auditory, and kinesthetic learning styles together on learning achievement with a significance value of 0.176 and 0.072